Studentâ€™s Perception of Building Drawing Techniques about Industrial Internship Program - Kurniawati, Mega; E. Nayono, Satoto; Dahar Minghat, Asnul; Rizal, Fahmi; ., .; ., . (International Journal of Engineering and Technology, 2018)
This study originated from the absence of career data from graduates of the Building Engineering Education Study Program at Padang State University. The purpose of this study is to describe and evaluate the implementation of the internship. Data collection techniques using questionnaires with Likert scale and data analysis techniques using descriptive analysis. The population in this study were students of the Building Image Engineering study program. The sampling technique uses total sampling with a sample of 25 respondents. The results of the study with indicators of student perceptions of the implementation of the 80.52% apprenticeship are categorized very well, and the indicator of the benefits of 83.20% apprenticeship is categorized very well.Â  Â